ANALYSIS OF THE RELATIONSHIP BETWEEN SELF EFFICACY AND HEALTHY LIVING ‎CONCIOUSNESS TOWARD SCIENCE LEARNING OUTCOME‎ - Kusumah, Raden Gamal Tamrin; Munandar, Achmad (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2017)
This study aimed to analyze the correlation between Self-Efficacy (SE), Health Awareness (KHS) and Science Learning Outcomes (HB) on environmental pollution subject in Junior High School. Subjects in this study were 7th grade junior high school students in Bandung Regency which is located near to the market and the railway stationenvironment. The research method has been used was quasi-experimental. The research design has been used was The Matching -Posttest Only - Control Group Design. Experimental class received the treatment, it was motivation and knowledge of healthy living, while the control group was not given. The data collection instruments has been used was three instruments, it was; 1) Self-Efficacy (SE) Instrument, 2) Health Awareness (KHS) Instrument, 3) Learning Outcomes (HB) Instrument. Results showed that the experimental class gain a higher value of self-efficacy, health awareness and learning outcomes better than the control class. Results of correlation test showed that there is a positive correlation between self-efficacy (SE) with health awareness (KHS), self-efficacy (SE) with learning outcomes (HB), and health awareness (KHS) with learning outcomes (HB). Keywords : Health Awareness; Self-Efficacy; Science Learning Outcomes; Environmental Pollution